On demand coalescence in microchannel: Viscosity matters. (23rd November 2019) - Simone, Giuseppina; van de Donk, Oole
Graphical abstract: Highlights: Coalescence in the outer fluid of homologous and non-homologous droplets was studied. Rheological properties of the outer fluids triggered or inhibited coalescence. Viscous and/or inertial coalescence developed according to the inner fluid properties. The dynamics of coalescence showed dependence on the ratio of viscosities of the inner and outer fluid. The coalescence develops by inertia or by the pure viscous regime. Abstract: Here, the coalescence of similar and dissimilar droplets has been investigated in microfluidics while varying the rheological and physical properties (e.g. viscosity, density) of the fluids. Our data indicate that in early regimes, the dynamics of coalescence depends on the properties of the inner fluid, which can generate a dominant viscous or inertial regime, while the outer fluid controls the activation or inhibition of the merging droplets. Besides, the models describing the mechanism in vacuum or in a very low viscous outer fluid become invalid when one of those conditions fails. An accurate modification resulted from accounting for the viscosity ratio of the inner and outer fluid. A phase diagram showing the crossovers into the different possible late-time dynamics identifies that, depending on the ratio of the viscosities of the inner and outer fluid, the coalescence develops by an inertial limited viscous, pure viscous or inertial regime.